2010
DOI: 10.1161/strokeaha.109.559880
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Studies of the Effect of Stroke on Incident Dementia

Abstract: Background and Purpose-Stroke is implicated in the incidence of dementia, and the risk of poststroke dementia is well characterized, but the excess risk of dementia in those with stroke compared with those without stroke is not well known. Methods-We conducted a systematic review of the excess risk of incident dementia conferred by stroke. Studies of the risk of incident dementia in the population with stroke compared with the population without stroke were identified and compared. Results-Sixteen studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
151
4
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(172 citation statements)
references
References 40 publications
(73 reference statements)
6
151
4
5
Order By: Relevance
“…Other researchers have also shown that many individuals diagnosed with dementia have a cerebrovascular cause or contribution to their impairments. 23 It would be difficult to obtain an accurate estimate of the overall prevalence of stroke survivors in Canada unless a comprehensive national survey was to ask questions similar to those that were covered by the Survey of Disability, Aging and Carers. Projecting future trends is notoriously difficult as the future prevalence depends on changes in the incidence of stroke, improvements in treatment, increases in population, and changes in the age structure of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have also shown that many individuals diagnosed with dementia have a cerebrovascular cause or contribution to their impairments. 23 It would be difficult to obtain an accurate estimate of the overall prevalence of stroke survivors in Canada unless a comprehensive national survey was to ask questions similar to those that were covered by the Survey of Disability, Aging and Carers. Projecting future trends is notoriously difficult as the future prevalence depends on changes in the incidence of stroke, improvements in treatment, increases in population, and changes in the age structure of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials and cognitive rehabilitation studies were excluded. Studies in which the only outcome was a diagnosis of dementia were excluded because this was the subject of a previous review 14. Studies were excluded if change in cognitive function over time in the stroke group was not reported (ie, studies that only compared cognitive outcomes in stroke patients versus controls were excluded).…”
Section: Methodsmentioning
confidence: 99%
“…There is a large amount of data about potential risk factors for AD, including age [1], genetics [2], and injury [3]. Many treatable medical conditions are also associated with an increased risk of AD, including stroke [4], diabetes [5], midlife hypertension [6], and hypercholesterolemia [7,8].…”
Section: Alzheimer's Diseasementioning
confidence: 99%